A Pamphlet and its (Dis)contents: A Case Study of Rangila Rasul and the Controversy Surrounding it in Colonial Punjab, 1923–29. (July 2015) - Raj, Richa
This article aims to study the communal tension generated by the publication of inflammatory literature by the extreme factions of two important religious groups in colonial Punjab, the Hindus and the Muslims. It would particularly examine the tension fuelled by the controversy surrounding the pamphlet entitled, Rangila Rasul, a product of the reformist zeal of an Arya Samajist, and attempts to gain political mileage from the controversy by the leaders of the 'victimised' community, in this case the Khilafatists and the Ahmadis. This paper would give a general impression of the effect such publications had on the masses who most of the times could not remain immune to religious attacks of this kind and study the judicial interpretation by the colonial state of Article 153A of the Indian Penal Code which dealt with such cheap productions of the 'gutter press', called so by the colonial government.